Don't trust the modern environmental epidemiologists! - H.-V. Ulmer (University of Applied Sciences in Tarnow, Poland, 2021)
Air pollution is responsible for more than 400.000 premature deaths/year in Europe - so German newspapers and other media complained at 9 September 2020, refering to the European Environment Agency [1]. If you ask the scientic base of this statement with severe political and economic consequences, you will find numerous studies since many years. Nearly all these studies describe "associations", "interactions" ore model calculations regarding air pollution and regional incidences, but for the author not a convincing proof for causality. Correlations don't proof causal interactions, they include a hight risk of stork-statistics. A similar case exist in the risk-level of NOx, decided by the EU as 40 μg/m3 (mean of year) to "protect human health and the environment" [2]. In Germany the MAK-value amounts to 950 μg/m3 (i.e. 23 times higher) for longlife expositions at workplaces, based on thorough toxicologic studies. There is a high interest of environmental politicans to propagate such "bad news" (400.000 deaths/year in Europe) and the public media like such news. So the author, claming about this scenario, got the followimg answer from the German ministry of health (23 September 2020 09:02): Usual toxikologic and clinical studies, often used to confirm a causality, are not suitable answering such questiions (with reference to Bradfort Hill criteria [3]). Why biomatical epidemiologists work on year after year for such research? Perhaps political and public attention garantee good chances for successful third-party-funding and acquisition of impact scores, very favorable in the actual scientific business. So the author is interested to discuss these considerations for getting new insights.